Relationship between the Expression of CD44v6 and Development,Progress, Invasion and Metastasis of Laryngeal Carcinoma - 刘邦华 孔维佳 龚树生 杨成章 汪广平 朱立新 (Current medical science, 2005)
The expression of CD44v6 and its relationship with the development, progress, invasion and metastasis of laryngeal carcinoma was investigated. The expression and content of CD44v6 mRNA in tissuess were detected by both RT-PCR and FCM which were respectivelyextracted from normal laryngeal mucosa, leukoplakia of larynx, laryngeal papilloma, polyp of vocal cord, tissues of laryngeal carcinoma, metastatic and nonmetastatic lymph nodes of neck, and tissues close to carcinoma. The outcome of RT PCR indicated that the expression rate of CD44v6 mRNA involved in tissues of laryngeal carcinoma and metastatic lymph nodes of neck was the highest (90 %- 100%) compared with that of leukoplakia of larynx, laryngeal papilloma, tissues close to carcinoma by 0.5cm (55.56%--60.00%) and that of normal laryngeal mucosa, polyp of vocal cord, nonmetastatic lymph nodes and tissues close to carcinoma by 1.0 cm was the lowest (13.33%--20%). The result from FCM was highly consistent with that from RT-PCR. It was suggested that CD44v6 was closely related with the development, progress, invasion and metastasis of laryngeal carcinoma. The outcome from the tissues close to carcinoma by different distance could do help to the determination of incisal edge in surgery abstractly.